Joubert Syndrome: Classic Sonographic Signs at 19 Weeks of Gestation - Singh, Divya; Kaur, Ladbans; Kaur, Meetanpreet; Kaur, Mangun (Journal of Fetal Medicine, 2016)
Joubert syndrome is a rare condition with an incidence of 1:100,000. It has primarily an autosomal recessive inheritance pattern. It is characterized by episodic hyperpnea, ataxia, hypotonia, abnormal eye movements, and varying degrees of intellectual disability. The causative genetic mutations are identifiable in only 50 % of the cases. Hence, neuroimaging in correlation with clinical features form the mainstay in the diagnosis of this entity. The classic imaging appearance is the ‘molar-tooth’ sign in the midbrain which was first described on MRI. The fourth ventricle has a bat-wing or umbrella-like configuration. Our case illustrates the classic imaging signs of Joubert syndrome at 19 weeks of gestation.
Keywords: Joubert; Molar-tooth; Bat wing ventricle; Vermis; Fourth ventricle